2004
DOI: 10.1021/es049125k
|View full text |Cite
|
Sign up to set email alerts
|

Particle Phase Acidity and Oligomer Formation in Secondary Organic Aerosol

Abstract: A series of controlled laboratory experiments are carried out in dual Teflon chambers to examine the presence of oligomers in secondary organic aerosols (SOA) from hydrocarbon ozonolysis as well as to explore the effect of particle phase acidity on SOA formation. In all seven hydrocarbon systems studied (i.e., alpha-pinene, cyclohexene, 1-methyl cyclopentene, cycloheptene, 1-methyl cyclohexene, cyclooctene, and terpinolene), oligomers with MW from 250 to 1600 are present in the SOA formed, both in the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
400
6
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 378 publications
(428 citation statements)
references
References 18 publications
20
400
6
2
Order By: Relevance
“…[33][34][35][36][37][38][39][40] The exact role of VOCs in the nucleation process is a subject of debate, although the fact that biogenic VOCs are much more reactive than anthropogenic VOCs 41 suggests that they play a role from the outset. Also, the acidity of seed particles appears to enhance the formation of SOA, [42][43][44] which may mean that current organic particle formation rates from natural emissions are greater than they would be under natural conditions because of the presence today of global anthropogenic inorganic acidic pollution.…”
Section: Emissions Of Pom From Forests and Othermentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40] The exact role of VOCs in the nucleation process is a subject of debate, although the fact that biogenic VOCs are much more reactive than anthropogenic VOCs 41 suggests that they play a role from the outset. Also, the acidity of seed particles appears to enhance the formation of SOA, [42][43][44] which may mean that current organic particle formation rates from natural emissions are greater than they would be under natural conditions because of the presence today of global anthropogenic inorganic acidic pollution.…”
Section: Emissions Of Pom From Forests and Othermentioning
confidence: 99%
“…Gao et al (2004) assigned the MW 358 α-pinene/O 3 compound to a dehydration product formed between the gem-diol forms of two norpinonic acid molecules. Iinuma et al (2004) reported MW 354 and 370 α-pinene/O 3 products that were enhanced in acidic conditions and tentatively assigned them to reaction products between the gem-diol of pinonaldehyde and pinonaldehyde, and between pinonaldehyde and hydroxypinonaldehyde, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Higher-MW products either correspond to non-covalent dimers between monomeric carboxylic acids that are held together by hydrogen bonds (e.g., Hoffmann et al, 1998;Claeys et al, 2009) or to covalent dimers between monomeric carboxylic acids that are connected through covalent bonds, such as, esters (e.g., Hamilton et al, 2006;Szmigielski et al, 2007;Müller et al, 2008) and oligomers formed through gem-diol intermediates (e.g., Gao et al, 2004;Iinuma et al, 2004;Tolocka et al, 2004;Docherty et al, 2005) or aldol condensation reactions (e.g., Tolocka et al, 2004). These heterogeneous processes are consistent 9384 F. Yasmeen et al: Terpenylic acid and related compounds: precursors for dimers in secondary organic aerosol with the observation that sulfuric acid seed aerosol catalyzes the formation of SOA (e.g., Jang et al, 2002Jang et al, , 2003Czoschke et al, 2003;Iinuma et al, 2004).…”
Section: Introductionmentioning
confidence: 99%